2023
DOI: 10.3390/genes14020528
|View full text |Cite
|
Sign up to set email alerts
|

Root Metabolism and Effects of Root Exudates on the Growth of Ralstonia solanacearum and Fusarium moniliforme Were Significantly Different between the Two Genotypes of Peanuts

Abstract: Wild peanut species Arachis correntina (A. correntina) had a higher continuous cropping tolerance than peanut cultivars, closely correlating with the regulatory effects of its root exudates on soil microorganisms. To reveal the resistance mechanism of A. correntina to pathogens, we adopted transcriptomic and metabolomics approaches to analyze differentially expressed genes (DEGs) and differentially expressed metabolites (DEMs) between A. correntina and peanut cultivar Guihua85 (GH85) under hydroponic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Multiple studies have shown variations in the structure of the rhizosphere microbiome, even within closely related plant genotypes, highlighting the importance of genotypespecific root exudates in forming associations with the corresponding microbiome [66][67][68][69][70][71][72]. While previous studies have observed qualitative distinctions in the root exudate profiles of Ler and Cvi, these profiles lack quantitative characterization [67].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown variations in the structure of the rhizosphere microbiome, even within closely related plant genotypes, highlighting the importance of genotypespecific root exudates in forming associations with the corresponding microbiome [66][67][68][69][70][71][72]. While previous studies have observed qualitative distinctions in the root exudate profiles of Ler and Cvi, these profiles lack quantitative characterization [67].…”
Section: Discussionmentioning
confidence: 99%